PENGARUH KESELAMATAN DAN KESEHATAN KERJA (K3) DAN PENGEMBANGAN KARYAWAN TERHADAP KINERJA KARYAWAN PADA PT TRIPARI TANGERANG - Mochamad Soelton; Lisa Budiyanti (Jurnal Ilmiah Manajemen dan Bisnis, 2017)
This study is a study of the occupational safety and health and employee development to employee performance at PT TRIPARI Tangerang, the study was conducted on 40 respondents using quantitative descriptive approach. By using two independent variables, occupational safety and health, development of employee and one dependent variable is the employee performance. This study aims to determine the effect of occupational safety and health (X1) and employee development (X2) on employee performance (Y).The results of this study indicate simultaneously (F test) variable occupational safety and health and development of employees together have a positive and significant impact on the employee performance, partially (t test) employee development has positive and significant impact on employee performance.